2013
DOI: 10.1136/bmjopen-2013-002644
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and self-reported health status among adolescents: a cross-sectional population-based study

Abstract: ObjectivesLittle is known about the dose–response relationship between physical activity and health benefits among young people. Our objective was to analyse the association between the frequency of undertaking moderate-to-vigorous physical activity (MVPA) and the self-reported health status of the adolescent population.DesignCross-sectional study.SettingAll regions of Spain.ParticipantsStudents aged 11–18 years participating in the Spanish Health Behaviour in School-aged Children survey 2006. A total of 375 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
67
4
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 43 publications
10
67
4
10
Order By: Relevance
“…Data from a large cross-sectional study of teenage females also found that PTSD diagnosis in adolescence was associated with poorer health outcomes, particularly more chronic conditions and reproductive health problems 9 . In our study, physical inactivity was significantly associated with health complaints, corroborating other studies, indicating a positive effect of physical activity on general health status 4,5,11,25,26 . The majority of studies investigated the role of physical activity in the relationship between school-related stress and adolescent health complaints 27,28 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Data from a large cross-sectional study of teenage females also found that PTSD diagnosis in adolescence was associated with poorer health outcomes, particularly more chronic conditions and reproductive health problems 9 . In our study, physical inactivity was significantly associated with health complaints, corroborating other studies, indicating a positive effect of physical activity on general health status 4,5,11,25,26 . The majority of studies investigated the role of physical activity in the relationship between school-related stress and adolescent health complaints 27,28 .…”
Section: Discussionsupporting
confidence: 92%
“…intrinsic motivation to be physically active), physical activity, and eating patterns may lead to psychosomatic complaints (headache, backache, and stomachache, among others) 3 . A recent study showed a protective effect of moderate-to-vigorous physical activity in both sexes among adolescents for four health indicators (self-rated health, health complaints, satisfaction with life, and health-related quality of life) 4 . In the latter study, associations between physical activity and health complaints were adjusted for health behaviors (smoking, alcohol intake), body mass index (BMI), dietary patterns (consumption of fruit and vegetables), screen time (TV and/or computer), parents' socioeconomic status (SES), and satisfaction with family and friends, while the study did not allow predicting associations with poor mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Our students with better academic performance compared to peers were more likely to achieve the MPA guideline, similar to findings among adolescents, where not having a high level of academic achievement was associated with higher noncompliance to PA recommendations (46). However, in Finland, self-reported PA was directly associated with academic achievement; but, objectively measured PA was not associated with academic achievement (12); and among first-year university students in Switzerland, better PA did not predict better learning goal achievement; and day-to-day PA was not related to daily learning goal achievement (47).…”
Section: Discussionsupporting
confidence: 83%
“…Positive benefits of regular physical activity, including positive effect on mental and physical health, are generally known (1,6,7). However, research suggests that many children do not reach recommended levels of physical activity (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%